Do I Contribute More When I Trust More? Differential Effects of Cognition- and Affect-Based Trust - CHUA, Roy Y. J. (Institutional Knowledge at Singapore Management University, 2006)
This study investigates the relationship between level of trust and cooperative behaviours in a social dilemma. We argue that this relationship should depend on the basis of trust (cognition- versus affect-based) and on beliefs about the equality of resource endowments. Results supported our prediction that increasing affect-based trust increases cooperation, but increasing cognition-based trust to a certain level can reduce cooperation because of free-riding tendency. Moreover, these effects of trust are stronger for individuals who believed that other group members had more resources than they did. Thus, our study demonstrates that higher levels of trust do not necessarily encourage cooperation. Implications of these findings are discussed.